Mission in Malawi : essays in honour of Klaus Fiedler - Nkhoma, Jonathan; Munyenyembe, Rhodian; Longwe, Hany; Fiedler, Klaus (Mzuni books, 2021)
"The first four essays in Mission in Malawi reassess the meaning, nature and place of mission in a postmodern world. Subsequent essays examine various issues that missionaries and the Church in Malawi have and continue to struggle with. These range from the problem of administering church discipline, the challenge of Bible translation, the question of how to deal with corruption in the corridors of power to the challenges of dealing with initiation rites, HIV/AIDS, patriarchy, gender inequality, the exercise of the Church's prophetic role, lack of contextualized theology, and the difficult task of creating an inclusive church and society. The last three essays are an attempt to describe a contextual theology appropriate for the African church, construct a theology for Malawi and project a future for mission in Malawi in the context of a changing world. These essays offer a rare window into the life and struggles of the Malawian Church even as it faces the postmodern future. The essays are not only informative but also challenging and thought-provoking. Scholars, students and other readers who share an interest in mission and the life of the Church in Malawi will find this collection of essays indispensable in the many years to come."--Publisher